Answer:
![x_(1) =4+2√(2)\\x_(2)=4-2√(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6nm7a5ctu7jmjp93a7e9p44c0wd0xl2ppf.png)
Explanation:
- 8x+ 8 = 0
we divide the coefficient of the X by half :
in this case: 8x/2 = 4 , then we do the following
to the result obtained (4) squared: 4^2=16
we sum and subtract by 16 to maintain the balance of equation:
- 8x+ 16-16+8 = 0
we have:
-16 +8=0
=16-8
= 8
we write the square root on both sides of the equation:
![\sqrt{(x-4)^(2)} = √(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n785k0heoerqcdmw9kg0kcu6t09lc9wc0g.png)
we know:
![\sqrt{a^(2)} = abs(a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bwvaxl06q9lceonjkhpjqnzt0c3v06koe3.png)
so we have:
abs(x-4)=
![\sqrt{2^(2)2 }](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d1qsnthxtamsct9qii7gj23nc97w53bmzq.png)
abs(x-4)=2
![√(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t462m14cxkj26cw9cmocfpgj44y1v8li5n.png)
we have:
![x_(1) -4 = 2√(2) \\\\x_(2) -4 =- 2√(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tdgiwv2yjwmoc5n5ohggn172g55zogdccg.png)
finally we have:
![x_(1) = 4+2√(2) \\\\x_(2) =4 - 2√(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1e3rbdw8qfvbesydvh50wq3xeb89mf47fb.png)